A short fragment of mitochondrial DNA for the taxonomic identification of blow flies (Diptera: Calliphoridae) in northwestern South America (2023)
Blow flies are of medical, sanitary, veterinary, and forensic importance. Their accurate taxonomic identification is essential for their use in applied research. However, neotropical fauna has not been completely studied or described, and taxa identification without the required training is a difficult task. Additionally, the current morphological keys are not fitting to all extant taxa. Molecular-based approaches are widely used to overcome these issues, including the standard 5ʹ COI barcode fragment (~650 base pairs [bp]) for identification at the species level. Here, a shorter sequence of 5ʹ COI fragment (~342 bp) was assessed for the identification of 28 blow fly species inhabiting the northwest of South America. One tree-based (the generalized mixed Yule-coalescent—GMYC) and 3 distance-based approaches (automatic barcode gap discover – ABGD, the best close match – BCM, and the nearest neighbor – NN) analyses were performed. Noticeably, the amplification and sequencing of samples that had been preserved for up to 57 years were successful. The tree topology assigned 113 sequences to a specific taxon (70% effectiveness), while the distance approach assigned to 95 (59% effectiveness). The short fragment allowed the molecular identification of 19 species (60% of neotropical species except for the Lucilia species and Hemilucilia semidiaphana). According to these findings, the taxonomic and faunistic considerations of the blow fly fauna were provided. Overall, the short fragment approach constitutes an optimal species confirmation tool for the most common blow flies in northwestern South America.